Manajemen Pemasaran Outlet Cuci Sepatu Ngumbah Shoes : Laporan Kegiatan Kuliah Kerja Lapangan - Moch. Falcha Omar Ali; Harsono Teguh; Rina Dewi; Diana Zuhro; Sutini Sutini (Jurnal Pengabdian Masyarakat, 2024)
Entrepreneurship is a creative business that is formed based on innovation to create something new, has added value, provides benefits, creates jobs and the results are useful for other people. Entrepreneurship is always confused with Medium Enterprises, although this is not always the case, because not always the business owned by an entrepreneur is classified as a Micro, Small and Medium Enterprise (MSME). Micro, Small and Medium Enterprises (MSMEs) can be interpreted in various ways by various sources. The basis for formulating the meaning of MSMEs can be based on the amount of business results/income, the amount of capital, the number of workers and the form of business. Micro, Small and Medium Enterprises (MSMEs) apparently have an important role in making a positive contribution to overcoming economic, social problems, in the form of high levels of poverty, large numbers of unemployed people, especially among people with low education, inequality in income distribution, uneven development processes between urban and rural areas and the problem of urbanization with all its negative impacts.